Advanced Optics for Defense Applications: UV Through LWIR III 2018
DOI: 10.1117/12.2304608
|View full text |Cite
|
Sign up to set email alerts
|

Advances in infrared GRIN: a review of novel materials towards components and devices

Abstract: Novel optical materials capable of advanced functionality in the infrared will enable optical designs that can offer lightweight or small footprint solutions in both planar and bulk optical systems. UCF's Glass Processing and Characterization Laboratory (GPCL) with our collaborators have been evaluating compositional design and processing protocols for both bulk and film strategies employing multi-component chalcogenide glasses (ChGs). These materials can be processed with broad compositional flexibility that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…where n and V correspond to the refractive index and volume fraction of the composite's phases, respectively. 42,45,51,54 While simplistic and approximate, this relationship has been shown to reasonably estimate the effective optical properties observed in optical nanocomposites made up of glass and crystalline phase(s) in the glass ceramics formed from parent glass to spatially transform a medium to realize a new optical function. It is important to note that the remaining residual glass phase will be modified by the departure of the crystal-forming constituents, thus resulting in a modified postprocessed glassy phase refractive index, and due to the subtle nature of this depletion, this composition and index change are difficult to experimentally quantify.…”
Section: Grin Via Spatially Controlled Nucleation and Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…where n and V correspond to the refractive index and volume fraction of the composite's phases, respectively. 42,45,51,54 While simplistic and approximate, this relationship has been shown to reasonably estimate the effective optical properties observed in optical nanocomposites made up of glass and crystalline phase(s) in the glass ceramics formed from parent glass to spatially transform a medium to realize a new optical function. It is important to note that the remaining residual glass phase will be modified by the departure of the crystal-forming constituents, thus resulting in a modified postprocessed glassy phase refractive index, and due to the subtle nature of this depletion, this composition and index change are difficult to experimentally quantify.…”
Section: Grin Via Spatially Controlled Nucleation and Growthmentioning
confidence: 99%
“…Recently, optical nanocomposites based upon multicomponent GAP-Se glasses have been shown to yield high-refractive index Pb-containing nanocrystalline phases in an amorphous matrix, which can remain stable at elevated temperatures or under photo/electronically excited states. 14,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] The effective refractive index, n eff , of the resulting glass ceramic nanocomposite increases monotonically with an increase in the volume fraction of the high-refractive index crystalline phase(s), thereby enabling creation of a homogeneous effective refractive index change in the starting glass. The glass ceramic composite's effective index can be approximated by knowledge of the refractive index of the residual amorphous and induced crystal phase(s) formed as well as their respective volume fractions, as calculated by E Q -T A R G E T ; t e m p : i n t r a l i n k -; s e c 2 .…”
Section: Grin Via Spatially Controlled Nucleation and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Other IR-GRIN methods have recently been demonstrated that do not rely on diffusion of glass elements. 21 Selective ceramization exploits the refractive index change that occurs when specially formulated chalcogenide glasses undergo crystallization. 22 This can be spatially controlled using laser-induced nucleation 23 and thermally controlled nucleation and growth 24 to create GRIN profiles.…”
Section: Introductionmentioning
confidence: 99%